(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
The historiographical path that begins with the world-economy concept of Federigo Melis and Fernand Braudel has gradually explored the organization of markets and the connections between commercial circuits and economic actors. In the 1990s, interest shifted towards regional and local spaces, with increasing attention to institutions and economic conjunctures in the links between markets of different levels. In 2000, Horden and Purcell suggested that the medieval Mediterranean was fragmented into microcosms, but with a substantial unity guaranteed by port connections and local trade. Subsequent studies have deepened the role of politics in market expansion and the Mediterranean as a network of short- and medium-range trade. In 2018, the ‘Datini Foundation’ stimulated reflections on ports as nodes of international exchanges. This framework of studies provides a basis for investigating the functioning of the commercial networks of Francesco Datini’s workshop, which was more than a retail outlet in 14th-century Tuscany. It was integrated into the European trade system, playing a crucial connective role between local, regional, and international markets.